Relationship between Blood Lead Levels and Hematological Parameters in Children from Al-Fallujah City in Iraq - Asmaa A. Shukur; Dawser K.Ismail; Kawther M. Ibrahim (College of Pharmacy University of Baghdad, 2017)
Environmental exposures to lead remain a serious problem in the developing and industrializing countries. Children are the highest risk aged-group for lead poisoning. This study was designed to assess lead exposure in Al-Fallujah city by analyzing blood lead levels in children and adults and to explain the relationship between blood lead levels, hematological parameters and ferritin levels in the children. The study was performed on-(90) subjects, (65children and 25 adults).Venous blood samples were taken for estimation of hematological parameters, serum ferritin levels and blood lead levels. The children group was subdivided into four groups as: group (A) (low ferritin, low Hb), group (B) (low ferritin, normal Hb), group (C) (normal ferritin, low Hb) and healthy control group (D) (normal ferritin, normal Hb).The results of this study demonstrating that all children groups: group (A) (n=14), group (B) (n=7), group(C) (n=17) and group (D) (n=27) had blood lead levels above the acceptable level 10Âµg/dl. There was significant increase in blood lead levels (10%) in the control group of children compared to adult group (P<0.05). In addition showed a significant increase in blood lead levels(52%)in group (A) and (29%) in group(C) compared with control group(P<0.001,P<0.01) respectively, while no significant increase in blood lead levels was shown in group (B). Thus the current study showed that elevated mean blood lead level above the acceptable limit of (10Âµg/dl) in all children groups, suggesting that iron deficiency anemia may amplify the effect of lead contamination in the environment. Key words: Blood lead levels, Hematological parameters, Ferritin, Iron deficiency anemia